A typological investigation of Nepalese languages - Donahue, Mark (Gipan, 2019)
The languages of Nepal are established as belonging to four families, with the recent addition of Austroasiatic speakers in the east. This paper moves away from language classification into genealogical families, and examines the classification of the languages of Nepal by examining their morphosyntactic features and applying computational methods.